Interstitial modification of palladium for partial hydrogenation reactions - Ellis, I (2016)
Heterogeneous catalysis is a key industrial process involved in the synthesis of nearly all chemicals currently produced. The environmental impact of these processes is huge so improvements must be made to current catalysts. Should a new material provide better yields at lower energy cost the benefits to both the industry and the planet are significant. There are many ways to change the behaviour of a catalyst, the addition of dopants, the selective blocking of active sites, and changing the strength of the support interaction to name a few. One technique that has become increasingly investigated is interstitial modification, the insertion of a light element into a metal lattice to change the metal’s catalytic properties. The work presented in this thesis devises greener synthetic routes to the known Pd-interstitialB/C catalyst and investigates potential routes to a novel interstitial material, Pd-interstitialLi/C. Initially, successful verification of interstitial modification comes from the characteristic increase in palladium lattice parameter from 3.89 to 4.00 Å and the blocking of the β-hydride formation. Initial catalytic screening determines the synthetic route which yields the most active catalyst which subsequently undergoes thorough characterisation. The wealth of evidence generated confirms the interstitial location of lithium within the palladium lattice, as well as adding to the current understanding of the Pd-interstitialB/C material. EELS analysis on Pd-interstitialB is the closest to direct observation of boron within the palladium lattice to date. PDF on Pd-interstitialLi shows 13.7 % of the palladium octahedral interstitial sites are occupied by lithium. This is the first report of interstitial lithium within palladium to date. The effect of the interstitial modification on catalytic hydrogenation by two elements that have opposite effects on the surface electronics of the host palladium gives intriguing results. The effect on catalysis varies depending on the conditions investigated. This bank of hydrogenation data allows an informed choice as to which interstitial material would be best suited to the gas or liquid phase catalytic hydrogenation under investigation.